2022
DOI: 10.1021/acsaelm.2c01075
|View full text |Cite
|
Sign up to set email alerts
|

Broadband Photosensitive Medium Based on Amorphous Equichalcogenides

Abstract: A photosensitive medium based on amorphous equichalcogenide thin films containing germanium and antimony is proposed with characteristics promising for applications in all-chalcogenide photonics, sensors, and photovoltaics. Optical properties, temperature, and exposure wavelength dependence of DC electrical conductivity are shown to be comparable with those for halide perovskites, which potentially makes amorphous equichalcogenides a very attractive alternative. The change in dark resistivity with temperature … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 53 publications
0
7
0
Order By: Relevance
“…The lone pair ( lp ) electrons of chalcogen atoms (S, Se, and Te) contribute to a density-of-state maximum at binding energy (BE) ∼2 eV. The density-of-state maximum at about 5 eV occurs due to the broadening of S 3 p , Se 4 p , and Te 5 p bonding state peaks by the chalcogen–Ge/Bi bonds. , Metal–metal bonds (like Ge–Ge, Ge–Bi, or Bi–Bi) should have their dominant contribution at ∼3.5 eV, which can be ascertained from a comparison to the XPS valence band spectra of other ChG. , A remarkable feature of the engineered Bi-modified thin film is the presence of higher density of states at the top of the valence band and near 3.5 eV compared with Bi-containing parent bulk glass (Figure ). It can explain the observed peculiarities in DC conductivity and enhanced temperature dependence of photocurrent.…”
Section: Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The lone pair ( lp ) electrons of chalcogen atoms (S, Se, and Te) contribute to a density-of-state maximum at binding energy (BE) ∼2 eV. The density-of-state maximum at about 5 eV occurs due to the broadening of S 3 p , Se 4 p , and Te 5 p bonding state peaks by the chalcogen–Ge/Bi bonds. , Metal–metal bonds (like Ge–Ge, Ge–Bi, or Bi–Bi) should have their dominant contribution at ∼3.5 eV, which can be ascertained from a comparison to the XPS valence band spectra of other ChG. , A remarkable feature of the engineered Bi-modified thin film is the presence of higher density of states at the top of the valence band and near 3.5 eV compared with Bi-containing parent bulk glass (Figure ). It can explain the observed peculiarities in DC conductivity and enhanced temperature dependence of photocurrent.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Using this approach, most of the binary and ternary ChG systems have been studied, and compositional dependences of major physical/chemical properties have been documented throughout their entire glass-forming regions. Mixing more than three constituents in multicomponent ChG composition opens a wider range of possibilities for improving and tailoring the medium properties, but simultaneously complicates the understanding of the ChG structure. Recent advances in the multicomponent ChG have led to the discovery of so-called ‘equichalcogenide’ family (ChG containing three chalcogens S, Se, and Te, simultaneously) with unique properties that can be explored in the all-chalcogenide photonic/electronic integrated platforms. , The multifunctional platforms that are based on a single-family material are very appealing because they can combine various effects in one medium using the same technological process. In particular, it is shown that amorphous materials of Ge–Sb–S–Se–Te equichalcogenide family can combine a high thermal stability, IR transparency, high sensitivity to the external influences (radiation, light, temperature) and phase-change memory effect .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is also on the lower side of E g values reported for Ge–Te or Ge–Sb–Te glass systems 46 . Advantage of equichalcogenide glass is the possibility to tune the optical gap in wider than pure GST ranges by changing S and Se concentration 39 . Moreover, together with quite high thermal stability of ~ 126 K (so-called Dietzel criterion) 47 , determined from 10 K/min DSC heating curve (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In this work, we introduce a new class of PCMs based on Sb-rich germanium equichalcogenides (containing equal amount of S, Se and Te) with total content of chalcogen atoms less than 50 at%. The physical properties of the discovered Ge 15 Sb 40 S 15 Se 15 Te 15 bulk glasses and thin films are investigated and compared to the earlier research on Ge 20 Sb 20 S 20 Se 20 Te 20 composition from the same Ge–Sb–S–Se–Te equichalcogenide family, in which thin films show a superior photosensitivity to the visible and NIR light in a broad temperature interval without any phase change effects below 200 °C 39 . Just a simple change in the Sb content makes it possible to obtain a phase-change material within the same Ge–Sb–S–Se–Te equichalcogenide family, which testifies a true multifunctionality of the proposed glass matrix.…”
Section: Introductionmentioning
confidence: 98%